Carbohydrate Ingestion During Prolonged Exercise Blunts the Reduction in Power Output at the Moderate-to-Heavy Intensity Transition - Dudley-Rode, H; Zinn, C; Plews, DJ; Charoensap, T; Maunder, E (Springer Science and Business Media LLC, 2024)
Purpose: To determine the effect of carbohydrate ingestion during prolonged exercise on durability of the moderate-to-heavy-intensity transition and severe-intensity performance. Methods: Twelve trained cyclists and triathletes (10 males, 2 females; V˙O2peak, 59 ± 5 mL kg−1 min−1; training volume, 14 ± 5 h week−1) performed an incremental test and 5-min time trial (TT) without prior exercise (PRE), and after 150 min of moderate-intensity cycling, with (POSTCHO) and without (POSTCON) carbohydrate ingestion. Results: Power output at the first ventilatory threshold (VT1) was lower in POSTCHO (225 ± 36 W, ∆ -3 ± 2%, P = 0.027, n = 11) and POSTCON (216 ± 35 W, ∆ -6 ± 4%, P = 0.001, n = 12) than PRE (229 ± 37 W, n = 12), and lower in POSTCON than POSTCHO (∆ -7 ± 9 W, ∆ -3 ± 4%, P = 0.019). Mean power output in the 5-min TT was lower in POSTCHO (351 ± 53 W, ∆ -4 ± 3%, P = 0.025) and POSTCON (328 ± 63 W, ∆ -10 ± 10%, P = 0.027) than PRE (363 ± 55 W), but POSTCHO and POSTCON were not significantly different (∆ 25 ± 37 W, ∆ 9 ± 13%, P = 0.186). Blood glucose concentration was maintained in POSTCHO, and was significantly lower at the 120 and 150-min timepoint in POSTCON (P < 0.05). Conclusion: These data suggest that durability of the moderate-to-heavy-intensity transition is improved with carbohydrate ingestion. This has implications for training programming and load monitoring.
Keywords: Carbohydrate; Durability; Exercise; Nutrition; 42 Health Sciences; 4207 Sports Science and Exercise; 1106 Human Movement and Sports Sciences; Sport Sciences; 3202 Clinical sciences; 3208 Medical physiology; 4207 Sports science and exercise; Humans; Male; Dietary Carbohydrates; Female; Adult; Exercise; Oxygen Consumption; Bicycling; Physical Endurance; Athletic Performance; Humans; Dietary Carbohydrates; Exercise; Oxygen Consumption; Physical Endurance; Bicycling; Adult; Female; Male; Athletic Performance; Humans; Male; Dietary Carbohydrates; Female; Adult; Exercise; Oxygen Consumption; Bicycling; Physical Endurance; Athletic Performance